Performance evaluation of traditional timber joints under cyclic loading and their influence on the seismic response of timber frame structures - Poletti, Elisa (2016)
Timber joints represent the governing part of a timber structure, particularly when assessing its seismic response. In order to better assess the seismic capacity of traditional timber frame structures, particularly timber-framed shear walls, pull-out and in-plane cyclic tests were carried out on their joints (half-lap joints). The aim is to better understand the influence of the joints on the walls and their influence on failure mechanisms and capacity. Their seismic characterisation was obtained via the analysis of the hysteretic behaviour and dissipative capacity of both unreinforced and retrofitted joints (using self-tapping screws, steel plates and GFRP sheets). Results show that all strengthening techniques were able to improve the dissipative and load-bearing capacity, but care should be taken into not over-stiffening the joints, as it would lead to an overly rigid structure.